Skrining Faktor Risiko Penularan Penyakit Tuberculosis Paru di RW 001 di Puskesmas Kelurahan Kedaung Kali Angke - Yohanes Firmansyah; Hendsun Hendsun; Edwin Destra; Bayu Aditya (Yayasan Pendidikan Medika Indonesia, 2021)
Background: Public health is influenced by four factors namely behavioural factors, environmental factors, heredity and health service factors. A very dense settlement and poor sanitation can lead to the occurrence of environmental-based diseases such as pulmonary tuberculosis (TB). This study aims to look at aspects of economic conditions and the environment in the homes of TB, especially in RW 001 in the working area of ​​the Kedaung Kali Angke Village Health Center, Jakarta. Method: Survey research conducted at the homes of TB sufferers and their neighbors' homes. Data processing was carried out by looking at the results of the questionnaire, and the TB screening form, then intervening with sputum examination of respondents with TB symptoms. Results: There were 4.3% respondents with a history of previous TB disease, with a history of TB disease in the same household as 24.3% respondents. 64.3% of respondents roof top zinc/asbestos. There were 72.9% respondents who had ventilation less than 10% of the floor area and in terms of natural room lighting there were 64.3% respondents with less natural lighting. Conclusion: Some environmental factors that influence the incidence of pulmonary TB in RW 001 are the area of ​​the house that is lacking, solid occupancy, ventilation with less than 10% of the floor area and lack of natural lighting.